2010
DOI: 10.1002/ejlt.200900268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary glucosylceramide on dermatitis in atopic dermatitis model mice

Abstract: The effects of dietary plant and yeast cerebroside (glucosylceramide), a major sphingolipid in plants and yeast, on atopic dermatitis (AD) like symptoms were investigated in a mouse model. After 7 wk of feeding with a diet containing maize glucosylceramide, plasma IgE levels became significantly lower and in contrast, the levels of interleukin (IL)-12, which induces cellular immunity, became significantly higher in the AD mice than in the controls. However, the sphingolipid constituents of the skin fraction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…However, plant-derived SBs desaturated at C8 were not detected in mammalian tissues, indicating that sphingadienine obtained from daily dietary sources is poorly incorporated and reconstructed into complex sphingolipids in tissues [129]. Besides, the predominant plant-derived SB, 4E/8Z-sphingadienine, was not detected in the mouse skin after ingestion of maize-derived GlcCERs [12]. …”
Section: Digestion Absorption and Uptake By Keratinocytes Of Oral Pmentioning
confidence: 99%
See 2 more Smart Citations
“…However, plant-derived SBs desaturated at C8 were not detected in mammalian tissues, indicating that sphingadienine obtained from daily dietary sources is poorly incorporated and reconstructed into complex sphingolipids in tissues [129]. Besides, the predominant plant-derived SB, 4E/8Z-sphingadienine, was not detected in the mouse skin after ingestion of maize-derived GlcCERs [12]. …”
Section: Digestion Absorption and Uptake By Keratinocytes Of Oral Pmentioning
confidence: 99%
“…Considering the various reports on dietary sphingolipids, it is unlikely that the skin reutilizes the intact dietary CERs and/or SBs as major constituents of SC lipid lamellae [12,137]. Some of the reasons include the low recovery of the plant-specific SB in the lymph (indicating poor intestinal absorption of dietary GlcCERs) [134], the conversion of the majority of dietary sphingosine into palmitic acid during intestinal absorption [119,120,121], a very low level of absorption of plant-specific SB (explained by a selective efflux of plant SBs by P-glycoprotein) [108,129], not detecting the plant-specific SB (4,8-sphingadienine) in mammalian tissues [12], the similar skin barrier improving effect of GlcCERs and SPM [137], and the fact that the amount of GlcCERs ingested is too small to directly localize in the skin and enhance CER levels [103].…”
Section: Mechanisms Underlying Skin Barrier Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent findings revealed that dietary GluCer originating from higher plants can be hydrolyzed in the intestine and that the intact plant form of sphingoid bases is barely absorbed by the tissues [9,41]. Ono et al [42] reported that dietary maize and yeast GluCer did not alter the sphingoid base composition in the skin of NC mice. We speculate that dietary maize GluCer accomplishes its anti-inflammatory effect, not only by producing bio-active metabolic intermediates through the sphingolipid metabolic pathways, but also via the activation of sphingolipid metabolic enzymes that affect endogenous sphingolipids at the inflammatory site, because diverse metabolic intermediates of sphingolipids, including ceramide, sphingosine, sphingosine-1-phosphate and ceramide-1-phosphate are well known important and highly bioactive endogenous regulators, which are involved in a complex metabolism network and play critical roles in inflammation [43][44][45][46].…”
Section: Discussionmentioning
confidence: 96%
“…Ono et al [42] demonstrated that supplementation of 0.1% GluCer diet for 7-week prevented atopic dermatitislike symptoms in a mouse model by regulating the Th1/ Th2 balance. However, IFN-c, IL-4 and IgE levels, the markers of Th1/Th2 balance, were not notably affected by GluCer administration for 6 days in the present study.…”
Section: Discussionmentioning
confidence: 98%